PENILAIAN OBYEK DAN DAYA TARIK RIAM ASAM TELOGAH DIKECAMATAN NOYAN KABUPATEN SANGGAU UNTUK WISATA ALAM - Putri, Mauluni Nurindra; Nugroho R, Joko (Universitas Tanjungpura, 2014)
Noyan is one district in the Regency of Sanggau, West Kalimantan Province. In Noyan, there is a potential spot for nature tourism which is not known by the public. It is located in the village Telogah. That potential spot for tourism is called Riam Asam Telogah. Riam Asam Telogah has potential tourist attraction to visit, but until present time, there are no related agencies interested in developing that place for touris destination due to lack of specific Information relating to potential tourist destination in details. This study aims to assess the potential attractiveness of Riam Asam Telogah in Sanggau regency, West Kalimantan Province, for ecotourism. In The method used in this study is a scoring method based on the standard assessment of nature attraction and nature conservation PHKA 2003. The study used data collection with questionnaire and direct observation in the field. The result of study showed an average score of 716,29 obtained from the area of Riam Asam Telogah which earns score score of A meaning that Riam Asam Telogah is potential to develop as a nature tourism or ecotourism. Keywords : Assessment Standards, Object of Attraction, Ecotourism, Riam Asam Telogah